Being a mobile international postgraduate research student with family in the United Kingdom: Conflict, contestation and contradictions. Issue 3 (3rd April 2018) - Mwale, Shadreck; Alhawsawi, Sajjadllah; Sayed, Yusuf; Rind, Irfan. A.
Abstract: The internationalisation of higher education has influenced the dramatic rise in the mobility of students, academics and knowledge across borders. There has been growing research interest focusing on international students studying abroad. While the student experience is an area of education that is often researched, most research focuses on experiences of undergraduate students. Also in the context of international students, greater research emphasis has been placed on the academic experiences and support available for undergraduates. While such research is important, less attention has been paid to the non-academic experiences of International Post-Graduate Research Students with Families (IPGRSF). This article seeks to fill this gap by focusing on the social worlds of IPGRSF in the UK, examining students' nuclear family contexts that are often marginalised in discourse. The article legitimises the IPGRSF subaltern world by focusing on how students negotiate its demands; how they negotiate their roles as research students with their other roles as spouses and parents, and the interrelationships among these roles; and how the university as an institution interacts with the students' subaltern world. The findings show that language plays a significant role in shaping the process of mobility as well as influencing the students' and their families' integration and networking in the host country. Also, the findings suggest that students often had positive experiences at departmental level, but felt let down by the wider university support.